Find f(g(x)) f(x)=1/4x^2 , g(x)=-2x^2 , h(x)=4x^2

Math
, ,
Set up the composite result function.
Evaluate by substituting in the value of into .
Simplify the expression.
Tap for more steps…
Apply the product rule to .
Raise to the power of .
Cancel the common factor of .
Tap for more steps…
Factor out of .
Cancel the common factor.
Rewrite the expression.
Multiply the exponents in .
Tap for more steps…
Apply the power rule and multiply exponents, .
Multiply by .
Find f(g(x)) f(x)=1/4x^2 , g(x)=-2x^2 , h(x)=4x^2

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top